(untitled) (INNOVATIVE ECONOMY, 2024)
Sokhatska O.M., Zhyrii V.Yа. AUTOMATION AS AN INNOVATIVE METHOD OF MANAGING A TRADE NETWORK OF CLOTHING STORES Purpose. The aim of the article is the substantiation of necessity for the implementation of automation as a novel approach to the management of a retail chain of clothing stores. Methodology of research. The systematic approach, general and special research methods were used in the study, in particular: scientific abstraction, deduction and induction – to formulate a scientific hypothesis of work, laws and principles; formal and logical – to make theoretical generalizations, substantiate the research methodology, formulate conclusions; monographic – to study the automation of management of trade enterprises; system-structural – to consider the automation object as an integral set of elements of management of a trade network. Findings. The article describes the concept of automating the management of the trade network of stores. The expected effect of the automation of the management of the trade network of clothing stores was determined. It is considered how the automation of the management of the trade network of clothing stores works in practice. The list of equipment for the effective operation of the trade network of clothing stores is substantiated. The software that should be used to automate retail networks of clothing stores is considered. Originality. The scientific novelty is determined by the relevance of the research topic, since the work systematized and improved knowledge about automation as an innovative method of managing the trade network of clothing stores. Practical value. The practical significance of the obtained results lies in the possibility of using the provisions of work by specialists in the development of the automation system for the management of the clothing trade network. The programs under consideration can be used to automate retail chains of clothing stores. Key words: management innovation, trade network, clothing store, automation.